ETHANOL PRODUCTION FROM COCOYAM (Хanthosoma sagittifolium): APPLICATION OF THERMODYNAMIC-TOPOLOGICAL ANALYSIS - S. Serna-Loaiza; Yu. A. Pisarenko; C. A. Cardona (Тонкие химические технологии)
Cocoyam (Xanthosoma sagittifolium (L.) Schott) is a tropical plant of the family of Araceas. Nigeria, China and Ghana are the countries that currently own most of the world production of this plant. In Colombia, there are not extensive crops of this plant, but it is used for animal feeding mainly. The plant has an aerial part with a high content of protein (leaves) and a tuber with an average starch content about 25% w/w. Compared to others starchy raw materials, this is a high value. Due to this fact this first-generation starchy material could be considered as a possible feedstock for the production of ethanol. Process design must ensure that the most advanced concepts are applied at the design and processing stage for every raw material to ensure efficient and more sustainable processes. For this reason, thermodynamic-topological analysis was used for the design of the stage of the produced ethanol purification. This work presents the process of ethanol production using cocoyam tuber. The software Aspen Plus v8.6 (Aspen Technology, Inc., USA) was used for the techno-economic assessment, and the Waste Reduction Algorithm (WAR) of the Environmental Protection Agency of the EE.UU. (EPA) was used to measure the environmental performance. The obtained production cost was 1,6 USD per kilogram, and the environmental impact was very low. This is an excellent incentive to promote the application of this feedstock to obtain a feasible alternative for the production of ethanol. Additionally, the use of thermodynamic-topological analysis in the design stage of the purification stage of the process proved to be very useful and easily applied.